2015
DOI: 10.1055/s-0034-1399006
|View full text |Cite
|
Sign up to set email alerts
|

Lung Infarction Following Pulmonary Embolism: A Comparative Study on Clinical Conditions and CT Findings to Identify Predisposing Factors

Abstract: Purpose: The aim of this study was to identify factors predisposing to lung infarction in patients with pulmonary embolism (PE). Materials and Methods: We performed a retrospective analysis on 154 patients with the final diagnosis of PE being examined between January 2009 and December 2012 by means of a Toshiba Aquilion 64 CT scanner. The severity of clinical symptoms was defined by means of a clinical index with 4 classes. The pulmonary clot load was quantified using a modified severity index of PE as propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 8 publications
6
37
2
1
Order By: Relevance
“…A recent retrospective comparative study by Kirchner et al evaluated possible causes for infarction with no correlation with cardiac congestion, malignancy, chronic bronchitis, clot burden, age or severity of symptoms. The main predisposing factor was peripheral location of vascular occlusion rather than large proximal occlusions [4]. This coincides with prior studies which showed the occlusion of pulmonary vessels smaller than 3 mm are likely beyond the physiologic anastomosis of the pulmonary and bronchial arteries and are thus predisposed to ischemia and infarction [5,6].…”
Section: Discussionsupporting
confidence: 85%
“…A recent retrospective comparative study by Kirchner et al evaluated possible causes for infarction with no correlation with cardiac congestion, malignancy, chronic bronchitis, clot burden, age or severity of symptoms. The main predisposing factor was peripheral location of vascular occlusion rather than large proximal occlusions [4]. This coincides with prior studies which showed the occlusion of pulmonary vessels smaller than 3 mm are likely beyond the physiologic anastomosis of the pulmonary and bronchial arteries and are thus predisposed to ischemia and infarction [5,6].…”
Section: Discussionsupporting
confidence: 85%
“…Pulmonary thromboembolism (PTE) is the third leading cause of death related to cardiovascular disease, in which acute right ventricular failure and pulmonary infarction are the main complications (1). Some studies have reported that pulmonary infarction occurs in 29% to 32% of patients with PTE (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that pulmonary infarction occurs in 29% to 32% of patients with PTE (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular obstruction of the lung classically causes reversible pulmonary haemorrhage or irreversible pulmonary infarction . The incidence of pulmonary infarction was reported recently to be approximately 30% in cases of acute pulmonary embolism and 3–10% in cases of bronchogenic carcinoma …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Vascular obstruction of the lung classically causes reversible pulmonary haemorrhage or irreversible pulmonary infarction. [1][2][3][4]7 The incidence of pulmonary infarction was reported recently to be approximately 30% in cases of acute pulmonary embolism 8,9 and 3-10% in cases of bronchogenic carcinoma. 5,6,10 We have encountered previously the presence of distinctive lobule-sized myxomatous or fibrous alveolar wall thickening around infarctions, 10 including one case that showed radiologically diffuse pulmonary opacities.…”
Section: Introductionmentioning
confidence: 99%